1972
DOI: 10.2337/diab.21.5.301
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Alpha Cell Function in Diabetics Response to Insulin

Abstract: The extremely high levels of glucagon recently observed in dogs with severe alloxan-induced diabetes decline promptly and precipitously to normal as soon as exogenous insulin is infused. This suggests that the normal response of the pancreatic alpha cell to hyperglycemia requires the presence of circulating insulin. To determine if the relative hyperglucagonemia of human diabetics responds similarly to insulin repletion, the plasma glucagon response of ten adult-type diabetic patients to a large, predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
4

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 3 publications
1
42
4
Order By: Relevance
“…It has been shown that the administration of anti-insulin serum to perfused rat pancreas markedly increased glucagon secretion and abolished the ability of an increase in the glucose concentration to decrease glucagon secretion (27,33,34). Acute insulin deficiency in humans (35,36), as well as alloxan-or streptozotocininduced diabetes in animals, are associated with hyperglucagonemia (37). It is therefore likely that the decrease in intra-islet insulin contributed in some way to the increased glucagon secretion that we observed in response to mild hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the administration of anti-insulin serum to perfused rat pancreas markedly increased glucagon secretion and abolished the ability of an increase in the glucose concentration to decrease glucagon secretion (27,33,34). Acute insulin deficiency in humans (35,36), as well as alloxan-or streptozotocininduced diabetes in animals, are associated with hyperglucagonemia (37). It is therefore likely that the decrease in intra-islet insulin contributed in some way to the increased glucagon secretion that we observed in response to mild hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, pan-'Assay of glucagon became available after normals (nos. [1][2][3][4][5] and diabetics (nos. 1-12) had already been studied.…”
Section: Methods Animalsmentioning
confidence: 99%
“…However, impaired insulin secretion may not be the only factor responsible for the abnormal glucose metabolism. Fasting hyperglucagonemia (2,3), lack of suppression of plasma glucagon by glucose (4,5), and excessive glucagon responses to amino acids (2, 6, 7) have been reported to occur in diabetics. These observations suggest that abnormal pancreatic alpha-cell function may also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD patients both with and without type 2 diabetes display fasting hyperglucagonemia (Bernsmeier et al 2014, Junker et al 2016. In fact, the suppression of plasma glucagon in response to a meal or hyperglycemia is impaired or eliminated in prediabetic and diabetic individuals (Muller et al 1970, Unger et al 1972, Rohrer et al 2012, Foghsgaard et al 2016. Glucose-mediated inhibition of glucagon secretion from pancreatic alpha cells occurs indirectly and relies on paracrine signaling from insulin secreting beta cells (Le Marchand & Piston 2010).…”
Section: Introductionmentioning
confidence: 99%